Learning From Errors: Curriculum Guide for the Morbidity and Mortality Conference With a Focus on Patient Safety Concepts - Christine Garcia; Nirvani Goolsarran (Association of American Medical Colleges, 2016)
Abstract Introduction Morbidity and mortality conferences are Accreditation Council for Graduate Medical Education-required educational series that are part of all residency training programs. This conference offers trainees an opportunity to discuss patient cases where errors or complications may have occurred. Conventionally, most of the allotted time is spent on case presentation and therapeutic debates, which is a lost opportunity to teach fundamental principles of patient safety, error analysis, and strategies for system-wide improvement. The goal of this resource is to refocus the content of morbidity and mortality and transform it into a platform for teaching patient safety principles and emphasizing error reduction strategies. Methods It was delivered as a 1-hour workshop session once a month during usual conference times. The workshop includes a mortality case review followed by a small-group activity in which trainees are assigned specific safety tasks, including systematic analysis of an error, conducting root cause analysis, and resident peer review. Results Postsurveys demonstrated that 90% of the trainees either agreed or strongly agreed that the safety concepts they learned would likely improve the quality of care they provide to future patients. Discussion We learned that morbidity and mortality could be used to effectively teach principles of patient safety and could create system-wide improvements.